Evaluation of Basketball Sports Achievement Coaching Program at the Bangau Club Palembang City South Sumatera Indonesia - Prabu, Dinda Ayu Puspita; Hidayah, Taufiq; Nasuka, Nasuka (Journal of Physical Education and Sports, 2021)
This study evaluate: Context , background, vision-mission and objectives of the coaching program, Input , availability of human resources (HR), the feasibility of facilities and infrastructure and implementation funding sources, Process, implementation of training programs, the role of trainer performance , athletes, facilities and infrastructure, coordination between parties, consumption, and welfare, Products achievement. Results of research context, basketball achievement development program for Bangau is accordance with objectives of coaching program that has been carried out both in background and vision and mission, Input , has good human resources, facilities and infrastructure for Stork basketball club, the National standard is very good , and a good source of funds. Process, training program responsibility coach implementation of training program is not well structured , the recruitment athletes part of coach. running quite well, facilities and infrastructure is very good, coordination between related parties is good, and the welfare in it is good, Product , basketball achievement development program for Bangau club, regarding achievements that are benchmarks for success in last 5 years regional championship in 2015-2020,Bangau club has had achievements and has often participated in championship but is not stable.Conclusion from this research concludes that from the context and input it has been carried out well, while the process , implementation training program is quite good but not structured in running it, product, achievements are good enough because they often participate in championship, but achievements are good. found that it is unstable and not maximal at regional level .